2016
DOI: 10.1080/07391102.2016.1155172
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the interaction between nanodiamond and human hemoglobin by surface tension measurement and spectroscopy methods

Abstract: In this study, a novel method to probe molecular interactions and binding of human hemoglobin (Hb) with nanodiamond (ND) was introduced based on the surface tension measurement. This method complements conventional techniques, which are basically done by zeta potential and dynamic light scattering (DLS) measurements, near and far circular dichroism (CD) spectroscopy, intrinsic and extrinsic fluorescence spectroscopy. Addition of ND to Hb solution increased the surface tension value of Hb-ND complex relative to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…In general, intermolecular interacting forces between a ligand and a protein include hydrogen bonding, van der Waals interaction, electrostatic forces, and hydrophobic network. 43 The thermodynamic parameters such as enthalpy change (ΔH°), standard entropy change (ΔS°), and standard Gibbs free energy change (ΔG°) of interaction were determined using van't Hoff equation (Equation 3): 43…”
Section: Thermodynamic Parametersmentioning
confidence: 99%
“…In general, intermolecular interacting forces between a ligand and a protein include hydrogen bonding, van der Waals interaction, electrostatic forces, and hydrophobic network. 43 The thermodynamic parameters such as enthalpy change (ΔH°), standard entropy change (ΔS°), and standard Gibbs free energy change (ΔG°) of interaction were determined using van't Hoff equation (Equation 3): 43…”
Section: Thermodynamic Parametersmentioning
confidence: 99%
“…41 The interaction of nanodiamond and silicon dioxide NPs with Hb also showed secondary and tertiary structural changes of Hb. 42,43 It has been shown that fullerene NPs synthesized by different methods induce various impacts on human serum albumin and bovine serum albumin conformations. The crucial difference between the two investigations was the fabrication methods of fullerene NPs, and principal differences between the main NPs fabricated by the two methods were the NP size distributions.…”
Section: Discussionmentioning
confidence: 99%
“…A number of techniques such as nuclear magnetic resonance (NMR) spectroscopy [78], X-ray crystallography [79], circular dichroism spectroscopy [80], isothermal calorimetry [81], differential scanning calorimetry [82], fluorescence spectroscopy [83], and UV-visible spectroscopy [84] have been widely used for analyzing the protein-NP interactions. The NPinduced conformational changes and subsequent corona formation depends on several factors such as, protein type, NP type, size of NP, shape of NP, pH and the temperature.…”
Section: The Effect Of Np On the Protein Conformational Changesmentioning
confidence: 99%